Hydrogen sulfide adsorbent as well as preparation method and application thereof
By using hydrogen sulfide adsorbent with Si-O-M structure in the coal chemical VOCs atmosphere, the problems of low removal efficiency of H2S gas and decreasing catalyst activity in the prior art are solved, and the adsorption effect is achieved with high precision and good moisture resistance. The sustainability of the adsorbent is improved through the regeneration process.
Patent Information
- Application Number
- CN202311032414.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-16
- Publication Date
- 2025-02-21
AI Technical Summary
The prior art cannot effectively remove H2S gas in the VOCs atmosphere of coal chemical industry, especially in high humidity environments, resulting in a decrease in catalyst activity and an increase in operating energy consumption, and lacks sulfurization with good humidity resistance, high selectivity, high accuracy and renewable Hydrogen adsorbent.
By heat-treating a mixed solution of silicon source, transition metal salt, concentrated hydrochloric acid, ethanol, organic surfactant and water, a sol is formed, and a gel is formed by droplet addition of concentrated ammonia water, and finally a Si-O-M structure is obtained by drying and calcining hydrogen sulfide adsorbent.
High-precision adsorption and removal of H2S gas in high humidity environments are achieved, high activity and stability of the catalyst are ensured, and the adsorbent is regenerated through high-temperature oxidation reaction, with good stability and reusability.
Smart Images

Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of adsorbents, and in particular to a hydrogen sulfide adsorbent, a preparation method and use thereof. Background Art
[0002] The reduction and control of volatile organic compounds (VOCs) has been listed as a key issue in air pollution control. VOCs emitted by modern coal chemical industry are mainly low-carbon alkanes with large air volume and low concentration, accompanied by hydrogen sulfide (H2S) gas (10mg / Nm 3 The following) and a large amount of water. Catalytic combustion technology is one of the most effective means of treating gaseous organic matter such as VOCs. Its core material is a sulfur-resistant catalyst with high stability and good activity. At present, the research on catalytic materials at home and abroad is mainly focused on the catalytic oxidation of single pollutants, and the sulfur resistance of catalysts needs to be improved. There is a lack of efficient sulfur-resistant catalysts targeting the emission characteristics of coal chemical VOCs (hydrocarbons, H2S gas, etc.). Among them, one of the feasible technical routes is to first remove the H2S gas from the coal chemical VOCs to be treated gas containing H2S gas by selective adsorption, thereby avoiding the stringent requirements of the catalyst for sulfur resistance.
[0003] According to literature reports (Yu Zhang, Peter Glarborg, Martin P. Andersson, Keld Johansen, Thomas K. Torp, Anker D. Jensen, Jakob M. Christensen, Sulfur poisoning and regeneration of Rh-ZSM-5 catalysts for total oxidation of methane, Applied Catalysis. B: Environmental, 2020, 227, 119176.), VOCs catalysts have low tolerance to sulfides and their activity is easily affected by sulfide concentration. For example, the above literature shows that when the SO2 concentration in the atmosphere reaches 10 mg / Nm 3 , the catalyst activity drops sharply, the operating temperature rises, and the operating energy consumption increases; when the SO2 concentration in the atmosphere reaches 1mg / Nm 3 The influence of SO2 on the catalyst is still not to be underestimated. The literature gives the influence of SO2 on the catalyst. H2S will also produce the same or even worse catalyst performance. Therefore, the concentration of H2S gas after removal should be lower than 1mg / Nm 3 .
[0004] In industry, H2S gas is mainly produced in oil field exploitation, natural gas purification, coal gas purification, etc. Commonly used adsorbents for removing H2S include large particle adsorbents such as zinc oxide, iron oxide, activated carbon, molecular sieves, etc. Later, metal organic framework compounds (MOFs) were also used as desulfurization adsorbents. The above desulfurization adsorbents can achieve a desulfurization accuracy of 10mg / Nm 3 -100 mg / Nm 3 However, the above mature products cannot meet the desulfurization accuracy requirements of the present invention. The desulfurization of coal chemical VOCs atmosphere (high humidity, containing H2S, containing VOCs) needs to achieve high accuracy (export concentration less than 1mg / Nm 3 ), high selectivity (selectively adsorbs H2S gas without adsorbing VOCs), and good water resistance (water and H2S gas will compete for adsorption).
[0005] Based on the phenomenon that transition metals with d-orbital electron vacancies can form complexes with the S element in H2S, transition metals with d-orbital electron vacancies (iron, cobalt, nickel, copper, zinc) are used to achieve high-precision H2S adsorption and removal. Since the specific surface area of the above-mentioned transition metal oxide particles or powders is small, there are few exposed transition metal adsorption sites, resulting in poor low-concentration H2S adsorption capacity and low precision.
[0006] Chinese patent CN109529795A discloses a hydrogen sulfide adsorbent and its preparation method, which utilizes the layered structure of magnesium aluminum hydrotalcite to form a high specific surface area. 2+ Ions make the adsorbent surface weakly alkaline. Magnesium-aluminum hydrotalcite can be used as an adsorbent for the adsorption and treatment of hydrogen sulfide gas in industrial waste gas, but the adsorption accuracy is difficult to reach 1mg / Nm 3 In addition, the adsorbent needs to be placed in a sodium carbonate solution with a concentration of 1 mol / L, soaked for 12 hours, and then separated into solid and liquid. The solid precipitate is placed at a temperature of 500°C and roasted for 5 hours to regenerate the hydrogen sulfide adsorbent, so the regeneration steps are cumbersome.
[0007] Chinese patent CN115055156A discloses a method for preparing a hydrogen sulfide adsorbent, which modifies a large amount of active copper ions on the surface of a MnO2-SiO2 composite gel, and generates CuS precipitates through the reaction of copper ions with hydrogen sulfide and attaches to the surface of the composite gel, thereby removing hydrogen sulfide through a chemical reaction mechanism, which can further improve the adsorption activity of the MnO2-SiO2 composite gel, increase its hydrogen sulfide capacity, and enhance the adsorption and removal effect of hydrogen sulfide. And due to the large specific surface area characteristics of the MnO2-SiO2 composite gel, the active copper ions can be evenly and widely distributed on the surface of the composite gel, which can give full play to the characteristics of the composite gel itself and copper ions in removing hydrogen sulfide, and can achieve a higher hydrogen sulfide adsorption accuracy. However, the Cu loaded in the adsorbent 2+In free state, free Cu 2+ It is only physically adsorbed and not embedded in the bulk phase of the carrier, and has no strong interaction with the interface. 2 + After forming CuS precipitation with H2S, it cannot be regenerated, and when there is water in the atmosphere, it will cause free Cu 2+ Dissolution, Cu on adsorbent 2+ Dissolved in water, reducing the adsorption effect.
[0008] Chinese patent CN112295544A discloses a hydrogen sulfide adsorbent with a modified metal organic compound skeleton, a preparation method and an application thereof, wherein the hydrogen sulfide adsorbent is obtained by heat treatment of a mixture of aluminum source, terephthalic acid, activated carbon and water, and then drying and calcining at high temperature. The hydrogen sulfide adsorbent has a high hydrogen sulfide adsorption capacity at room temperature, and is resistant to high temperatures and has good regeneration performance. However, as described in Chinese patent CN109529795A, activated carbon materials have a strong adsorption capacity for inorganic or organic substances in gases and solutions and colloidal particles, and the problem with the activated carbon adsorption treatment process is that the activated carbon is easily hardened after being dampened by water, and the specific surface area is greatly reduced, thereby affecting the treatment effect.
[0009] Therefore, there is still an urgent need in the art for a hydrogen sulfide adsorbent with good moisture resistance, high selectivity, high precision and regenerability. Summary of the invention
[0010] In view of the shortcomings of the prior art, the present invention aims to obtain a hydrogen sulfide adsorbent with good moisture resistance, high selectivity, high precision and renewability through material structure design and material preparation, so as to desulfurize the sulfur-containing VOCs atmosphere in advance, ensure the high activity and stability of the catalyst, meet the needs of catalytic oxidation technology in the degradation of VOCs in coal chemical industry, and ultimately better realize the purification of exhaust gas containing VOCs.
[0011] One of the purposes of the present invention is to provide a method for preparing a hydrogen sulfide adsorbent, comprising the following steps:
[0012] 1) heat-treating a mixed solution containing a silicon source, a transition metal salt, concentrated hydrochloric acid, ethanol, an organic surfactant and water to form a sol;
[0013] 2) adding concentrated aqueous ammonia dropwise to the sol obtained in step 1) to form a gel;
[0014] 3) Drying and calcining the gel obtained in step 2) to obtain a hydrogen sulfide adsorbent.
[0015] According to the preparation method of the present invention, in step 1), a silicon source is added to a solution in which a transition metal salt, concentrated hydrochloric acid, ethanol, an organic surfactant and water are evenly mixed to obtain a mixed solution containing the silicon source, transition metal salt, concentrated hydrochloric acid, ethanol, an organic surfactant and water.
[0016] According to the preparation method of the present invention, in step 1), under mechanical stirring, a silicon source is added to a solution in which a transition metal salt, concentrated hydrochloric acid, ethanol, an organic surfactant and water are uniformly mixed. Preferably, the stirring speed is 200-600 rpm.
[0017] According to the preparation method of the present invention, in step 1), the conditions for heat treatment are: reaction temperature is 20-90° C., and reaction time is 2-72 hours.
[0018] According to the preparation method of the present invention, in step 1), the silicon source is one or more of methyl orthosilicate, ethyl orthosilicate, propyl orthosilicate, butyl orthosilicate, and butyl silicate.
[0019] According to the preparation method of the present invention, in step 1), the transition metal salt is a nitrate or hydrochloride of iron, cobalt, nickel, copper or zinc, or a hydrate of a nitrate or hydrochloride of iron, cobalt, nickel, copper or zinc.
[0020] According to the preparation method of the present invention, in step 1), the organic surfactant is one or more of polyethylene glycol, polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123), hexadecyltrimethylammonium salt, and tetradecyltrimethylammonium salt.
[0021] According to the preparation method of the present invention, in step 1), the ethanol is anhydrous ethanol.
[0022] According to the preparation method of the present invention, in step 1), the water is deionized water.
[0023] According to the preparation method of the present invention, wherein, in step 1), the degree of polymerization of polyethylene glycol is 400-2000.
[0024] According to the preparation method of the present invention, in step 1), in parts by volume, the silicon source is 10-50 parts by volume, the concentrated hydrochloric acid is 0.1-10 parts by volume, the ethanol is 0-70 parts by volume, and the water is 2-70 parts by volume.
[0025] According to the preparation method of the present invention, in step 1), the molar ratio of the silicon source to the transition metal salt is 100:1-100:7, preferably 100:2-100:5, and more preferably 100:3-100:4.
[0026] According to the preparation method of the present invention, in step 1), the organic surfactant is 0.1-0.5 parts by weight per 1 part by volume of the silicon source (g / mL, kg / L).
[0027] According to the preparation method of the present invention, in step 2), the concentrated ammonia water is 2-20 parts by volume.
[0028] According to the preparation method of the present invention, in step 2), the dropping speed of the concentrated ammonia water is 1-20 parts by volume per minute.
[0029] According to the preparation method of the present invention, in step 2), concentrated aqueous ammonia is added dropwise to the sol obtained in step 1) under stirring, wherein the stirring speed is 200-600 rpm.
[0030] According to the preparation method of the present invention, in step 3), the drying conditions are: drying temperature is 60-120° C., and drying time is 6-24 hours.
[0031] According to the preparation method of the present invention, in step 3), the calcination conditions are: the calcination temperature is 400-600° C., and the calcination time is 2-6 hours.
[0032] A second object of the present invention is to provide a hydrogen sulfide adsorbent prepared according to the above-mentioned method for preparing the hydrogen sulfide adsorbent.
[0033] According to the hydrogen sulfide adsorbent of the present invention, the operating conditions for the hydrogen sulfide adsorbent to adsorb hydrogen sulfide are: relative humidity of the atmosphere is 0%-90%, operating temperature is 15°C-35°C, air is the balance gas, the total flow rate is 0.5 liters per minute-1.5 liters per minute, and the volume space velocity is 100,000 per hour-150,000 per hour.
[0034] According to the hydrogen sulfide adsorbent of the present invention, after the hydrogen sulfide adsorbent adsorbs hydrogen sulfide, the concentration of hydrogen sulfide in the volatile organic matter is less than or equal to 1 mg / Nm 3 , preferably less than or equal to 0.5 mg / Nm 3 .
[0035] According to the hydrogen sulfide adsorbent of the present invention, after the hydrogen sulfide adsorbent adsorbs hydrogen sulfide, a high-temperature oxidation reaction is performed to remove hydrogen sulfide to regenerate the hydrogen sulfide adsorbent, wherein the conditions of the oxidation reaction are: a heating rate of 1°C per minute to 5°C per minute, an oxidation reaction temperature of 300°C to 500°C, an oxidation reaction time of 0.5 hour to 1 hour, a compressed air flow rate of 0.05 liters per minute to 0.15 liters per minute, and a volume space velocity of 10,000 per hour to 15,000 per hour.
[0036] A third object of the present invention is to provide use of the hydrogen sulfide adsorbent of the present invention in hydrogen sulfide adsorption.
[0037] Beneficial Effects
[0038] The present invention adopts organic silicon as a silicon source. During the hydrolysis and dehydration condensation process of the organic silicon source, the metal ions dissolved in the solution are embedded in the network structure connected by Si-O bonds to form Si-OM (M represents five transition metals: iron, cobalt, nickel, copper and zinc), thereby achieving the following effects: 1. ensuring that the metal elements are dispersed in an ionic state, thereby improving the H2S adsorption accuracy; 2. avoiding the dissolution of free metal ions in a high-humidity environment, thereby improving the water resistance. Specifically, the adsorbent forms a Si-OM structure, and the complexing ability of H2S with M is stronger than that of water with M in a water-containing atmosphere, and it is easier for H2S to form a Si-OMS complexing structure with the Si-OM structure of the adsorbent; 3. facilitating the regeneration of the adsorbent, and the formed Si-OMS complexing structure can be formed again by removing S through high-temperature oxidation, and the hydrogen sulfide adsorbent of the present invention has good stability and reusability. In summary, the present invention obtains a hydrogen sulfide adsorbent with good moisture resistance, high selectivity, high precision and renewability, which can desulfurize the sulfur-containing VOCs atmosphere in advance, ensure the high activity and stability of the catalyst, meet the needs of catalytic oxidation technology in the degradation of VOCs in coal chemical industry, and ultimately better realize the purification of exhaust gas containing VOCs. DETAILED DESCRIPTION
[0039] The present invention is further described below in conjunction with embodiments, but the present invention is not limited to the embodiments listed.
[0040] Unless otherwise specified, the materials used in the following examples and comparative examples were purchased from conventional commercial sources.
[0041] Example 1
[0042] 1) Under mechanical stirring, a silicon source is added to a solution in which a transition metal salt, concentrated hydrochloric acid, ethanol, an organic surfactant and deionized water are uniformly mixed, and the stirring speed is 300 rpm;
[0043] 2) The silicon source is selected from ethyl orthosilicate, the organic surfactant is selected from polyethylene glycol with a degree of polymerization of 2000, and the transition metal salt is selected from copper nitrate hydrate;
[0044] 3) Measured by volume: 1 part by volume of concentrated hydrochloric acid, 2 parts by volume of deionized water, 67 parts by volume of ethanol, and 33 parts by volume of ethyl orthosilicate;
[0045] Measured in parts by weight, the amount of polyethylene glycol with a degree of polymerization of 2000 added is 10.89 parts by weight;
[0046] The molar ratio of ethyl orthosilicate to copper nitrate hydrate is 100:3.
[0047] 4) keeping the mixed solution under reflux at 85° C. for 12 hours;
[0048] 5) cooling the sol obtained in step 4) naturally to room temperature while keeping stirring;
[0049] 6) adding 13 parts by volume of concentrated aqueous ammonia dropwise to the sol obtained in step 5) at a dropping speed of 6.5 parts by volume per minute to obtain a wet gel, and stopping stirring;
[0050] 7) drying the wet gel obtained in step 6) at a drying temperature of 80° C. for 12 hours to obtain a dry gel;
[0051] 8) The dry gel obtained in step 7) was calcined at a temperature of 550°C for 5 hours, and then naturally cooled to obtain a hydrogen sulfide adsorbent A1. A1 was tested by XRD and showed a mantou peak at 20-30°, which was a peak of amorphous silicon dioxide. The sharp and narrow CuO characteristic peaks at around 35° and 38° did not appear, indicating that Cu and Si-O formed a Si-O-Cu structure.
[0052] 9) The penetration time of H2S in adsorbent A1 is 126 min, corresponding to an initial concentration of 10 mg / Nm 3 , penetration concentration is 0.5mg / Nm 3 , the relative humidity of the atmosphere is 90% at the working temperature, indicating that the material has good moisture resistance;
[0053] 10) After the penetration test in step 9), the adsorbent A1 adsorbed with H2S was desorbed in air at 300°C for 30 minutes, and naturally cooled to the operating temperature to complete an adsorption-desorption cycle; this was repeated 60 times. By comparing the penetration time of H2S in the adsorbent A1 for the 1st and 60th times, there was no decrease, and there was an upward trend. The 60th penetration time was 135 minutes. This shows that the material has good stability and reusability.
[0054] Example 2
[0055] 1) Under mechanical stirring, a silicon source is added to a solution in which a transition metal salt, concentrated hydrochloric acid, ethanol, an organic surfactant and deionized water are uniformly mixed, and the stirring speed is 300 rpm;
[0056] 2) The silicon source is selected from ethyl orthosilicate, the organic surfactant is selected from polyethylene glycol with a degree of polymerization of 2000, and the transition metal salt is selected from copper nitrate hydrate;
[0057] 3) Measured by volume: 1 part by volume of concentrated hydrochloric acid, 2 parts by volume of deionized water, 67 parts by volume of ethanol, and 33 parts by volume of ethyl orthosilicate;
[0058] Measured in parts by weight, the amount of polyethylene glycol with a degree of polymerization of 2000 added is 10.89 parts by weight;
[0059] The molar ratio of ethyl orthosilicate to copper nitrate hydrate is 100:1.
[0060] 4) keeping the mixed solution under reflux at 85° C. for 12 hours;
[0061] 5) cooling the sol obtained in step 4) naturally to room temperature while keeping stirring;
[0062] 6) adding 13 parts by volume of concentrated aqueous ammonia dropwise to the sol obtained in step 5) at a dropping speed of 6.5 parts by volume per minute to obtain a wet gel, and stopping stirring;
[0063] 7) drying the wet gel obtained in step 6) at a drying temperature of 80° C. for 12 hours to obtain a dry gel;
[0064] 8) The dry gel obtained in step 7) was calcined at a temperature of 550°C for 5 hours, and then naturally cooled to obtain a hydrogen sulfide adsorbent A2. A2 showed a mantou peak at 20-30° as a peak of amorphous silicon dioxide through XRD testing, and the sharp and narrow CuO characteristic peaks near 35° and 38° did not appear, indicating that Cu and Si-O formed a Si-O-Cu structure;
[0065] 9) The penetration time of H2S in adsorbent A2 is 81 min, corresponding to an initial concentration of 10 mg / Nm 3 , penetration concentration is 0.5mg / Nm 3 , the relative humidity of the atmosphere is 90% at the working temperature, indicating that the material has good moisture resistance;
[0066] 10) After the penetration test in step 9), the adsorbent A2 adsorbed with H2S was desorbed in air at 300°C for 30 minutes, and naturally cooled to the operating temperature to complete an adsorption-desorption cycle; this was repeated 60 times. By comparing the penetration time of H2S in the adsorbent A2 for the 1st and 60th times, there was no decrease, and there was an upward trend. The 60th penetration time was 85 minutes. This shows that the material has good stability and reusability.
[0067] Example 3
[0068] 1) Under mechanical stirring, a silicon source is added to a solution in which a transition metal salt, concentrated hydrochloric acid, ethanol, an organic surfactant and deionized water are uniformly mixed, and the stirring speed is 300 rpm;
[0069] 2) The silicon source is selected from ethyl orthosilicate, the organic surfactant is selected from polyethylene glycol with a degree of polymerization of 2000, and the transition metal salt is selected from copper nitrate hydrate;
[0070] 3) Measured by volume: 1 part by volume of concentrated hydrochloric acid, 2 parts by volume of deionized water, 67 parts by volume of ethanol, and 33 parts by volume of ethyl orthosilicate;
[0071] Measured in parts by weight, the amount of polyethylene glycol with a degree of polymerization of 2000 added is 10.89 parts by weight;
[0072] The molar ratio of ethyl orthosilicate to copper nitrate hydrate is 100:4.
[0073] 4) keeping the mixed solution under reflux at 85° C. for 12 hours;
[0074] 5) cooling the sol obtained in step 4) naturally to room temperature while keeping stirring;
[0075] 6) adding 13 parts by volume of concentrated aqueous ammonia dropwise to the sol obtained in step 5) at a dropping speed of 6.5 parts by volume per minute to obtain a wet gel, and stopping stirring;
[0076] 7) drying the wet gel obtained in step 6) at a drying temperature of 80° C. for 12 hours to obtain a dry gel;
[0077] 8) The dry gel obtained in step 7) was calcined at a temperature of 550°C for 5 hours, and then naturally cooled to obtain a hydrogen sulfide adsorbent A3. A3 was tested by XRD and showed a mantou peak at 20-30°, which was a peak of amorphous silicon dioxide. The sharp and narrow CuO characteristic peaks at around 35° and 38° did not appear, indicating that Cu and Si-O formed a Si-O-Cu structure.
[0078] 9) The penetration time of H2S in adsorbent A3 is 152 min, corresponding to an initial concentration of 10 mg / Nm 3 , penetration concentration is 0.5mg / Nm 3 , the relative humidity of the atmosphere is 90% at the working temperature, indicating that the material has good moisture resistance;
[0079] 10) After the penetration test in step 9), the adsorbent A3 adsorbed with H2S was desorbed in air at 300°C for 30 minutes, and naturally cooled to the operating temperature to complete an adsorption-desorption cycle; this was repeated 60 times. By comparing the penetration time of H2S in the adsorbent A3 for the 1st and 60th times, there was no decrease, and there was an upward trend. The 60th penetration time was 158 minutes. This shows that the material has good stability and reusability.
[0080] Example 4
[0081] 1) Under mechanical stirring, a silicon source is added to a solution in which a transition metal salt, concentrated hydrochloric acid, ethanol, an organic surfactant and deionized water are uniformly mixed, and the stirring speed is 300 rpm;
[0082] 2) The silicon source is selected from ethyl orthosilicate, the organic surfactant is selected from polyethylene glycol with a degree of polymerization of 2000, and the transition metal salt is selected from copper nitrate hydrate;
[0083] 3) Measured by volume: 1 part by volume of concentrated hydrochloric acid, 2 parts by volume of deionized water, 67 parts by volume of ethanol, and 33 parts by volume of ethyl orthosilicate;
[0084] Measured in parts by weight, the amount of polyethylene glycol with a degree of polymerization of 2000 added is 10.89 parts by weight;
[0085] The molar ratio of ethyl orthosilicate to copper nitrate hydrate is 100:7.
[0086] 4) keeping the mixed solution under reflux at 85° C. for 12 hours;
[0087] 5) cooling the sol obtained in step 4) naturally to room temperature while keeping stirring;
[0088] 6) adding 13 parts by volume of concentrated aqueous ammonia dropwise to the sol obtained in step 5) at a dropping speed of 6.5 parts by volume per minute to obtain a wet gel, and stopping stirring;
[0089] 7) drying the wet gel obtained in step 6) at a drying temperature of 80° C. for 12 hours to obtain a dry gel;
[0090] 8) calcining the dry gel obtained in step 7): the calcination temperature is 550° C., the calcination time is 5 hours, and the dry gel is naturally cooled to obtain a hydrogen sulfide adsorbent A4. A4 is tested by XRD and a steamed bun peak at 20-30° is a peak of amorphous silicon dioxide, and a CuO characteristic peak with a smaller peak intensity appears near 35° and 38°, indicating that Cu forms CuO nanoparticles on the surface of silicon oxide;
[0091] 9) The penetration time of H2S in adsorbent A4 is 86 min, corresponding to an initial concentration of 10 mg / Nm 3 , penetration concentration is 0.5mg / Nm 3 , the relative humidity of the atmosphere is 90% at the working temperature, indicating that the material has good moisture resistance;
[0092] 10) After the penetration test in step 9), the adsorbent A4 adsorbed with H2S was desorbed in air at 300°C for 30 minutes, and naturally cooled to the operating temperature to complete an adsorption-desorption cycle; this was repeated 60 times. By comparing the penetration time of H2S in the adsorbent A4 for the 1st and 60th times, there was no decrease, and there was an upward trend. The 60th penetration time was 88 minutes. This shows that the material has good stability and reusability.
[0093] Example 5 to Example 8
[0094] The preparation steps and test procedures are the same as those of Example 3, except for the types of metal salts selected. The metal salts selected in Examples 5 to 8 are respectively: iron nitrate, cobalt nitrate, nickel nitrate and zinc nitrate. Specifically, hydrates of the above metal salts are selected in Examples 5 to 8 of the present invention.
[0095] Example 9
[0096] The preparation steps and testing procedures are the same as those in Example 3, except that:
[0097] 1) Measured by volume: 0.1 parts by volume of concentrated hydrochloric acid, 2 parts by volume of deionized water, 0 parts by volume of ethanol, and 10 parts by volume of tetraethyl orthosilicate;
[0098] 2) The surfactant is polyethylene glycol with a polymerization degree of 400, measured by weight, and the added amount of polyethylene glycol with a polymerization degree of 400 is 1 part by weight.
[0099] Example 10
[0100] The preparation steps and testing procedures are the same as those in Example 3, except that:
[0101] 1) Measured by volume: 10 parts by volume of concentrated hydrochloric acid, 70 parts by volume of deionized water, 70 parts by volume of ethanol, and 50 parts by volume of tetraethyl orthosilicate;
[0102] 2) The surfactant is polyethylene glycol with a polymerization degree of 1500, measured by weight, and the added amount of polyethylene glycol with a polymerization degree of 1500 is 16.5 parts by weight.
[0103] Embodiment 11
[0104] The preparation steps and testing procedures are the same as those in Example 3, except that:
[0105] 1) Measured by volume: 1 part by volume of concentrated hydrochloric acid, 3 parts by volume of deionized water, 67 parts by volume of ethanol, and 33 parts by volume of tetraethyl orthosilicate;
[0106] 2) The surfactant is polyethylene glycol with a polymerization degree of 2000, measured by weight, and the added amount of polyethylene glycol with a polymerization degree of 2000 is 16.5 parts by weight;
[0107] Comparative Example 1
[0108] 1) Under mechanical stirring, a silicon source is added to a solution in which concentrated hydrochloric acid, ethanol, an organic surfactant and deionized water are uniformly mixed, and the stirring speed is 300 rpm;
[0109] 2) The silicon source is selected from ethyl orthosilicate, and the organic surfactant is selected from polyethylene glycol with a degree of polymerization of 2000;
[0110] 3) Measured by volume: 1 part by volume of concentrated hydrochloric acid, 2 parts by volume of deionized water, 67 parts by volume of ethanol, and 33 parts by volume of ethyl orthosilicate;
[0111] Measured in parts by weight, the amount of polyethylene glycol with a degree of polymerization of 2000 added is 10.89 parts by weight;
[0112] 4) keeping the mixed solution under reflux at 85° C. for 12 hours;
[0113] 5) cooling the sol obtained in step 4) naturally to room temperature while keeping stirring;
[0114] 6) adding 13 parts by volume of concentrated aqueous ammonia dropwise to the sol obtained in step 5) at a dropping speed of 6.5 parts by volume per minute to obtain a wet gel, and stopping stirring;
[0115] 7) drying the wet gel obtained in step 6) at a drying temperature of 80° C. for 12 hours to obtain a dry gel;
[0116] 8) calcining the dry gel obtained in step 7): the calcination temperature is 550° C., the calcination time is 5 hours, and the dry gel is naturally cooled to obtain a hydrogen sulfide adsorbent S1. The XRD test of S1 shows a mantou peak at 20-30°, which is a peak of amorphous silica;
[0117] 9) The penetration time of H2S in adsorbent S1 is 11 min, corresponding to an initial concentration of 10 mg / Nm 3 , penetration concentration is 0.5mg / Nm 3 , the relative humidity of the atmosphere is 90% at the working temperature, and the penetration time of the adsorbent S1 obtained in comparative example 1 in a high humidity atmosphere is very short, indicating that the material does not have good moisture resistance and adsorption performance;
[0118] 10) After the breakthrough experiment in step 9), the adsorbent S1 adsorbed with H2S was desorbed in air at 300°C for 30 minutes, and naturally cooled to the operating temperature to complete an adsorption-desorption cycle; this was repeated 60 times. By comparing the breakthrough time of H2S in the adsorbent S1 for the 1st and 60th times, there was no decrease, and the breakthrough time for the 60th time was 11 minutes.
[0119] Comparative Example 2
[0120] 1) Under mechanical stirring, a silicon source is added to a solution in which a transition metal salt, concentrated hydrochloric acid, ethanol, an organic surfactant and deionized water are uniformly mixed, and the stirring speed is 300 rpm;
[0121] 2) The silicon source is selected from ethyl orthosilicate, the organic surfactant is selected from polyethylene glycol with a degree of polymerization of 2000, and the transition metal salt is selected from copper nitrate hydrate;
[0122] 3) Measured by volume: 1 part by volume of concentrated hydrochloric acid, 2 parts by volume of deionized water, 67 parts by volume of ethanol, and 33 parts by volume of ethyl orthosilicate;
[0123] Measured in parts by weight, the amount of polyethylene glycol with a degree of polymerization of 2000 added is 10.89 parts by weight;
[0124] The molar ratio of ethyl orthosilicate to copper nitrate hydrate is 100:10.
[0125] 4) keeping the mixed solution under reflux at 85° C. for 12 hours;
[0126] 5) cooling the sol obtained in step 4) naturally to room temperature while keeping stirring;
[0127] 6) adding 13 parts by volume of concentrated aqueous ammonia dropwise to the sol obtained in step 5) at a dropping speed of 6.5 parts by volume per minute to obtain a wet gel, and stopping stirring;
[0128] 7) drying the wet gel obtained in step 6) at a drying temperature of 80° C. for 12 hours to obtain a dry gel;
[0129] 8) calcining the dry gel obtained in step 7): the calcination temperature is 550°C, the calcination time is 5 hours, and the dry gel is naturally cooled to obtain the hydrogen sulfide adsorbent S2. The XRD test of S2 shows that the mantou peak at 20-30° is the peak of amorphous silicon dioxide, and the sharp and narrow CuO characteristic peaks appear near 35° and 38°, indicating that Cu forms CuO nanoparticles on the surface of silicon oxide;
[0130] 9) The penetration time of H2S in adsorbent S2 is 36 min, corresponding to an initial concentration of 10 mg / Nm 3, penetration concentration is 0.5mg / Nm 3 , the relative humidity of the atmosphere is 90% at the working temperature, and the penetration time of the adsorbent S2 obtained in Example 2 in the high humidity atmosphere is very short, indicating that the material does not have good moisture resistance and adsorption performance;
[0131] 10) After the breakthrough experiment in step 9), the adsorbent S2 adsorbed with H2S was desorbed in air at 300°C for 30 minutes, and naturally cooled to the operating temperature to complete an adsorption-desorption cycle; this was repeated 60 times. By comparing the breakthrough time of H2S in the adsorbent S2 for the 1st and 60th times, there was no decrease, and there was an upward trend. The breakthrough time for the 60th time was 38 minutes.
[0132] Testing of hydrogen sulfide adsorption performance of the hydrogen sulfide adsorbent of the present invention
[0133] The hydrogen sulfide adsorption performance test was carried out on a fixed bed reactor (quartz tube, inner diameter 8 mm), and the gas concentration at the gas outlet was monitored online by an infrared spectrometer (USA, MKS). The initial gas concentration was obtained by passing the gas through an empty quartz tube. The adsorbent sample was granulated and screened to obtain 40-60 mesh particles totaling 0.5 grams. The 0.5 gram sample was placed in a quartz tube and fixed at both ends with quartz wool, and then the adsorbent was evaluated.
[0134] ① The atmosphere composition before adsorption is as follows: H2S concentration is 10 mg / Nm 3 , the relative humidity of the atmosphere is 90%, the operating temperature is 35°C, air is the balance gas, the total flow rate is 1 liter per minute, and the volume space velocity (GHSV) is 120,000 per hour.
[0135] ② The adsorbent was regenerated as follows: compressed air with a total flow rate of 0.1 liters per minute and a headspace velocity (GHSV) of 120,000 per hour. The reactor was heated by a tubular furnace at a heating rate of 2°C per minute to 300°C.
[0136] The H2S adsorption performance of the examples and comparative examples is shown in Table 1 below.
[0137] Table 1
[0138]
[0139]
[0140] According to the records of the examples and comparative examples, the adsorbent is used at an initial concentration of 10 mg / Nm 3 H2S atmosphere (balance gas is air), penetration concentration is 0.5mg / Nm 3 , the working temperature is room temperature (25-30℃), the relative humidity of the atmosphere is 90%, and the airspeed is 120,000h -1. It can be seen from Examples 1 to 8 that inorganic salts (iron, cobalt, nickel, copper, zinc) as adsorbent additives have good adsorption-desorption cycle stability; when copper salts are selected as adsorbent additives, they have better adsorption performance and good moisture resistance. In particular, according to Example 3, when the molar ratio of silicon to copper is 100:4, the adsorption penetration time is up to 152 minutes, and after 60 cycles of adsorption-desorption, the adsorption performance increases to 158 minutes. It can be seen from Examples 9 to 11 that when the silicon and copper elements are in the optimal molar ratio of 100:4, adjusting the amount of concentrated hydrochloric acid, ethanol, polyethylene glycol and the degree of polymerization parameters of polyethylene glycol will produce a small change in the adsorption performance of the adsorbent. When the degree of polymerization of the surfactant (polyethylene glycol) used is high, it is beneficial to enrich the pore structure of the gel, promote gas mass transfer and expose more adsorption sites, and enhance the adsorption effect, such as Example 11, but its performance improvement is small. The reasons are as follows: although the area of exposed active sites is increased, the amount of copper elements is limited and the adsorption performance cannot be improved as the area increases; when the concentration of the surfactant is low and the amount used is small, the area of exposed adsorption sites is small and the adsorption effect is reduced to a certain extent, such as Example 9 and Example 10; as shown in Example 9 to Example 11, hydrochloric acid and deionized water are used. Too little dosage will cause the ethyl orthosilicate to be unable to decompose or decompose slowly, so that the metal ions cannot be embedded in its chemical structure, which is easy to cause the dissolution of metal ions to reduce the adsorption effect. When the amount of hydrochloric acid and deionized water used is too much, the ethyl orthosilicate will decompose and agglomerate rapidly, which will also lead to the occurrence of the above results. Similarly, too little ethyl orthosilicate is difficult to provide a sufficient number of sites for anchoring metal ions, and too much leads to rapid decomposition and agglomeration; the amount of ethanol determines the mutual solubility of ethyl orthosilicate and water. Less ethanol dosage will cause part of the ethyl orthosilicate and the aqueous solution to be unable to decompose, and too much ethanol leads to the waste of high-value ethanol and the increase of cost. In addition, by adjusting other parameters within the scope of this application, such as the type of silicon source, transition metal salt and organic surfactant, heat treatment temperature and time, concentrated ammonia water dosage, concentrated ammonia water drop acceleration, stirring speed, drying temperature and time, calcination temperature and time, etc., the adsorption performance of the obtained adsorbent is better than that of the comparative example, and the above parameters are adjusted to improve the adsorption performance by 2 to 16 times compared with the comparative example.
[0141] Comparative Example 1 is an adsorbent without adding metal salt components. The adsorption performance is the lowest and the adsorption performance remains unchanged after cyclic adsorption-desorption for 11 minutes; when the molar ratio of silicon element: copper element is 100:10, which exceeds the preferred range of the present invention (100:1-100:7), the hydrogen sulfide performance does not increase with the increase of copper content, but decreases instead.
Claims
1. A method for preparing a hydrogen sulfide adsorbent, comprising the following steps: 1) heat-treating a mixed solution containing a silicon source, a transition metal salt, concentrated hydrochloric acid, ethanol, an organic surfactant and water to form a sol; 2) adding concentrated aqueous ammonia dropwise to the sol obtained in step 1) to form a gel; 3) Drying and calcining the gel obtained in step 2) to obtain a hydrogen sulfide adsorbent.
2. The preparation method according to claim 1, wherein In step 1), Adding a silicon source to a solution in which a transition metal salt, concentrated hydrochloric acid, ethanol, an organic surfactant and water are uniformly mixed to obtain a mixed solution containing the silicon source, the transition metal salt, concentrated hydrochloric acid, ethanol, an organic surfactant and water; Preferably, under mechanical stirring, the silicon source is added to a solution in which the transition metal salt, concentrated hydrochloric acid, ethanol, an organic surfactant and water are uniformly mixed.
3. The preparation method according to claim 1, wherein In step 1), the heat treatment conditions are: reaction temperature is 20-90° C., and reaction time is 2-72 hours.
4. The preparation method according to any one of claims 1 to 3, wherein In step 1), The silicon source is one or more of methyl orthosilicate, ethyl orthosilicate, propyl orthosilicate, butyl orthosilicate, and butyl silicate; The transition metal salt is a nitrate or hydrochloride of iron, cobalt, nickel, copper, or zinc, or a hydrate of a nitrate or hydrochloride of iron, cobalt, nickel, copper, or zinc; The organic surfactant is one or more of polyethylene glycol, polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, hexadecyl trimethyl ammonium salt, and tetradecyl trimethyl ammonium salt; Ethanol is anhydrous ethanol; The water is deionized water.
5. The preparation method according to claim 4, wherein In step 1), the degree of polymerization of polyethylene glycol is 400-2000.
6. The preparation method according to any one of claims 1 to 3, wherein In step 1), In parts by volume, the silicon source is 10-50 parts by volume, the concentrated hydrochloric acid is 0.1-10 parts by volume, the ethanol is 0-70 parts by volume, and the water is 2-70 parts by volume; The molar ratio of the silicon source to the transition metal salt is 100:1-100:7, preferably 100:2-100:5, more preferably 100:3-100:4; The organic surfactant is present in an amount of 0.1-0.5 parts by weight per 1 part by volume of the silicon source.
7. The preparation method according to any one of claims 1 to 3, wherein In step 2), The concentrated ammonia water is 2-20 parts by volume; The drop rate of the concentrated ammonia solution is 1-20 parts by volume per minute; The concentrated ammonia water is added dropwise to the sol obtained in step 1) under stirring, wherein the stirring speed is 200-600 rpm.
8. The preparation method according to any one of claims 1 to 3, wherein In step 3), The drying conditions are: drying temperature is 60-120°C, and drying time is 6-24 hours; The calcination conditions are: calcination temperature is 400-600°C, and calcination time is 2-6 hours.
9. A hydrogen sulfide adsorbent prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the hydrogen sulfide adsorbent prepared by the preparation method according to any one of claims 1 to 8 in hydrogen sulfide adsorption.
Citation Information
Patent Citations
Hydrogen sulfide adsorbent and preparation method thereof
CN109529795A
Hydrogen sulfide adsorbent with modified metal organic compound framework as well as preparation method and application thereof
CN112295544A
Preparation method of hydrogen sulfide adsorbent
CN115055156A